Faktor-Faktor yang Berhubungan dengan Kelengkapan Imunisasi Dasar pada Batita di Desa Hutaimbaru Kecamatan Halongonan Kabupaten Padang Lawas Utara Tahun 2016 - Zuriatina Chairani Nainggolan; Rahayu Lubis; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Immunization remains a public health problem in North Padang Lawas District, because the basic immunization coverage is low and has not achieved Universal Child Immunization (UCI) in most of these areas. One of them Hutaimbaru village with basic immunization coverage amounted to 30% in 201. This research is an analytic observational (non-experimental) with cross sectional study design, aimed to analyze the factors related to the completeness of basic immunization by toddlers on Hutaimbaru subdistricts Halongonan in 2016. The study population was all mother who had a toddler in the village of the Hutaimbaru subdistrict Halongonan and sampling done by total sampling. Data were collected using a questionnaire and analyzed using Chi-square test and multiple logistic regression test. Immunization coverage complete of the result of this study was 48.6%. The results evidence that the variables have a significant related (p<0,05) on the completeness of immunization in toddlers in the Hutaimbaru village of the subdistrict Halongonan 2016 is the age variable (p= 0,008), education (p. = 0,0001), occupation (p= 0,0001), and parity (p= 0,001), when the unrelated variables (p<0,05) is a variable place of birth (p= 0,110) and the distance of a residence with health care (p= 0,364). The results of multiple logistic regression test, the variables have a significant most related on the completeness of immunization in toddlers in the Hutaimbaru village of the subdistrict Halongonan in 2016 is education (Exp B= 7,280). Implementation of the integrated health system should apply first date alone each month, so that mothers more easily remember, or Implement s system of “Jemput Bola” in providing basic immunization, given the extensive settlements Hutaimbaru village is not so wide, and they can be easy to reach. Keywords: Immunization, Hutaimbaru, Toddlers